NMR Structure of a Triangulenium‐Based Long‐Lived Fluorescence Probe Bound to a G‐Quadruplex. (31st August 2016) - Kotar, Anita; Wang, Baifan; Shivalingam, Arun; Gonzalez‐Garcia, Jorge; Vilar, Ramon; Plavec, Janez
Abstract: An NMR structural study of the interaction between a small‐molecule optical probe (DAOTA‐M2) and a G‐quadruplex from the promoter region of the c‐myc oncogene revealed that they interact at 1:2 binding stoichiometry. NMR‐restrained structural calculations show that binding of DAOTA‐M2 occurs mainly through π–π stacking between the polyaromatic core of the ligand and guanine residues of the outer G‐quartets. Interestingly, the binding affinities of DAOTA‐M2 differ by a factor of two for the outer G‐quartets of the unimolecular parallel G‐quadruplex under study. Unrestrained MD calculations indicate that DAOTA‐M2 displays significant dynamic behavior when stacked on a G‐quartet plane. These studies provide molecular guidelines for the design of triangulenium derivatives that can be used as optical probes for G‐quadruplexes.